Women empowerment and reproductive health outcomes in Malawi - Chimanga, Daisy N (My University, 2014)
Background Many countries in sub Saharan Africa face high fertility rates and rapid population growth rates. With a total fertility rate of 5.7, Malawi is no exception. High population growth rate has consequently challenged Malawi’s social and economic development.The purpose of this study is to examine the relationship between women empowerment and the reproductive health outcome of fertility. Methods This is a secondary data analysis of the Malawi Demographic and Health Survey of 2010 (MDHS, 2010).Atotal of 13 333 women aged 15-49 was extracted from the MDHS for purposes of this study.To meet the objectives of the study, data analysis was done in three stages – univariate, bivariate and multivariate analysis. Stata version 12 was used for management and analysing the data. Results Study findings show that 60 percent of Malawian women are in the low empowered group and only 40 percent are in the high empowered group. Multivariate analysis results show that there is no significant relationship between fertility and empowerment. Conclusion The multivariate results show that there is no significant relationship between women empowerment and fertility in Malawi. However there is still need to encourage women to be empowered as a way of reducing poverty levels in Malawi.
A Research Project Submitted To the School Of Humanities, University Of Witwatersrand, Johannesburg, in Partial Fulfillment Of The Requirements for the Degree of Masters of Arts in The Field Of Demography and Population Studies